The role of vitamins and minerals on the symptoms of premenstrual syndrome: A narrative review - Maryam Farahmand; Fahimeh Ramezani Tehrani; Marzieh Saei Gharenaz (Mashhad University of Medical Sciences, 2022)
Introduction: Premenstrual syndrome is one of the most common menstrual disorders in women at reproductive age. This syndrome affects women's quality of life and reduces their efficiency. On the other hand, the main cause is not known, various factors such as lifestyle, type of nutrition, and hormones affect it. Since vitamins and minerals have been suggested as possible factors affecting the severity of symptoms of this syndrome, so this study was conducted with aim to investigate the effect of vitamins and minerals on the symptoms of the syndrome. Methods: In this narrative review study, to find the related studies, databases of SID, PubMed, and Google Scholar were searched according to the keywords including premenstrual syndrome, premenstrual syndrome symptoms, minerals, and vitamins from 1980 to 2020. The clinical trial and review studies which were published and the language of them was English or Persian were selected. Results: Some vitamins such as vitamin E, B6, D and some minerals such as magnesium, zinc, and calcium have a positive effect on the symptoms of premenstrual syndrome. Conclusion: Since the optimal consumption of vitamins and minerals promotes general health, the results of this narrative review by identifying the challenges in this area, leads to the recognition and use of effective minerals and vitamins to reduce the symptoms of premenstrual syndrome. Keywords: